Selective Laser Trabeculoplasty for Steroid-Induced Ocular Hypertension following Endothelial Keratoplasty. (3rd October 2022) - Davidson, Max; Berkowitz, Eran; Roberts, Harry; Wanas, Ahmed; Myerscough, James
Abstract: Purpose: To examine the safety and efficacy of selective laser trabeculoplasty (SLT) in patients responding to topical steroids with elevated intraocular pressure following endothelial keratoplasty. Methods: Patients that underwent Descemet Membrane Endothelial Keratoplasty (DMEK) or Descemet Stripping Automated Endothelial Keratoplasty (DSAEK) were offered SLT as first-line therapy if they presented with steroid response and met inclusion criteria. Patient demographics, best-corrected visual acuity (BCVA), steroid and glaucoma regimens were recorded before and after SLT. Results: Twelve eyes of eight patients were recruited to the study. All patients demonstrated a reduction in IOP and only one patient remained on anti-glaucoma drops after SLT. The mean (±SD) reduction in IOP following SLT was 8.8 (±4.9) mmHg ( p < 0.0001). BCVA remained stable and no adverse events following treatment were observed. Conclusions: SLT may be a safe and effective treatment option that reduces topical antihypertensive burden while allowing continuance of corticosteroids in steroid-responsive eyes at high risk of rejection following endothelial keratoplasty. Larger randomized studies are needed to compare SLT efficacy with topical medication in this patient group and to review any impact on graft survival and glaucoma progression.